Association Between Body Weight Variation and Survival and Other Adverse Events in Critically Ill Patients With Shock: A Multicenter Cohort Study of the OUTCOMEREA Network. Issue 10 (October 2018) - Gros, Antoine; Dupuis, Claire; Ruckly, Stéphane; Lautrette, Alexandre; Garrouste-Orgeas, Maité; Gainnier, Marc; Forel, Jean-Marie; Marcotte, Guillaume; Azoulay, Elie; Cohen, Yves; Schwebel, Carole; Argaud, Laurent; et al.
Abstract : Objectives: This study in critically ill patients with shock assessed the prognostic value of body weight variations occurring each day from day 3 to day 7 on the 30-day outcome in terms of mortality, occurrence of ventilator-associated pneumonia and of bedsore, and occurrence of length of stay. Design: Retrospective analysis of data. Multivariate subdistribution survival models were used at each day, from day 3 to day 7. The impact of body weight variations on length of stay was estimated through a multivariate negative binomial regression model. Setting: Prospective multicenter cohort study. Patients: Critically ill patients admitted in ICU with shock and requiring mechanical ventilation within 48 hours. Intervention: None. Measurements and Main Results: Two-thousand three-hundred seventy-four patients were included. Their median body weight variations increased from 0.4 kg (interquartile range, 0–4.8 kg) on day 3 to 3 kg (interquartile range, –0.4 to 8.2 kg) on day 7. Categories of body weight variations were defined depending on body weight variations interquartiles: weight loss, no weight gain, moderate and severe weight gain. A severe weight gain tended to be associated with death at days 5 and 6 (day 5: subdistribution hazard ratio, 1.27; 95% CI, 0.99–1.63; p = 0.06 and day 6: subdistribution hazard ratio, 1.43; 95% CI, 1.08–1.89; p = 0.01), a weight loss tended to be associated with bedsore, and a severe gain between at days 5 and 6 was associated with ventilator-associated pneumonia. Any body weight variations were associated with an increased length of stay. Conclusions: In survivors at day 3, body weight variations during the first days of ICU stay might be a clinically relevant tool to prevent weight gain but also for prognostication of 30-day mortality, occurrence of ventilator-associated pneumonia, and occurrence of prolonged ICU stay. Abstract : Supplemental Digital Content is available in the text.